The development of live microorganism-based oxygen shuttles for enhanced hypoxic tumor therapy - Han, Dandan; Zhang, Xing; Ma, Yichuan; Yang, Xinjian; Li, Zhenhua (Materials today bio, 2023)
Hypoxia is a prominent feature of malignant tumors and contributes to tumor proliferation, metastasis, and drug resistance in various solid tumors. Therefore, improving tumor oxygenation is crucial for curing tumors. To date, multiple strategies, including oxygen delivering and producing materials, have been designed to increase the oxygen concentration in hypoxic tumors. However, the unsustainable supply of oxygen is still the main obstacle, resulting in a suboptimal outcome in treating oxygen-deprived tumors. Thus, a sufficient oxygen supply is highly desirable in the treatment of hypoxic tumors. Photosynthesis, as the main source of oxygen in nature through the conversion of light energy into chemical energy and oxygen, has been widely studied in scientific research. Moreover, photosynthetic microorganisms have been increasingly applied in cancer therapy by increasing oxygenation, which improves the therapeutic effect of oxygen-consuming tumor therapeutic tools such as radiotherapy and photodynamic therapy. In this review, we summarize recent advances in the design and manufacture of live bacteria as oxygen shuttles for a new generation of hypoxic tumor treatment strategies. Finally, current challenges and future directions are also discussed for successfully addressing hypoxic tumor issues. [Display omitted]